PIDANA PELAYANAN MASYARAKAT SEBAGAI ALTERNATIF BENTUK PIDANA DALAM MEWUJUDKAN PEMBARUAN HUKUM PIDANA ANAK - Sudarno (Paulus Law Journal, 2022)
The community service punishment was important to adopt as the alternative for the punishment form in the realization of the innovation of the child punishment law in Indonesia based on the arguments of: the Conformity of the Idea of the Community Service Punishment with the Restorative Judiciary Concept, the Conformity of the Idea of the Community Service Punishment with the Theory of the Punishment individualization, the Conformity of the Idea of the Community Service Punishment with the Trend of the International World Development, and the Conformity of the Idea of the Community Service Punishment with the Aims of the Condemnation and the Development of the Child Criminals.